GENETIC RELATIONSHIP BETWEEN SOME BARLEY GENOTYPES (HORDEUM VULGARE L.) USING SSR TECHNIQUE (MICROSATELLITE) - Al-khalaf , Kamal; Lawand, Salam; Al-mahasneh, Hussien (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The study was carried out in order to determine the degree of genetic kinship among fifteen barley genotypes using SSR technique with 14 pairs of primers. The study showed that, all the primers gave amplification products and showed polymorphism between the studied genotypes. The total number of alleles was 19, with an average of 1.35, and the number of polymorphic alleles was 19, the percentage of polymorphism was 100%. The number of total and polymorphic alleles ranged between one allele as the lowest value for primers (Bmac0209, Bmac0067, Bmag0225, Bmag012, Bmag0394, Bmag0353, Bmag0206, Bmac0031, GBM1362, EBmac0603) and three alleles as the highest value for the primer Bmag0006. The polymorphism information content (PIC) for each primer ranged from 0.32 (Bmac0209, Bmag0225) as the lowest value, to 0.721 (Bmag0385) as the highest value, and average PIC value was 0.446. The highest value of the percent agreement values (PAV) matrix was about 0.909, between Furat 7 and Mohsen White cultivars, which indicate the present of a high degree of genetic kinship, followed by the Furat 5 and Asowad Arabic (0.863), while the lowest value was 0.318 between H10 and Furat 4, indicating a great genetic variation between them. The previous results were in agreement with the genetic kinship analysis and cluster analysis which showed a high degree of genetic similarity between Furat 7 and Mohsen White, followed by Furat 5 and Asowad Arabic.